Post-TPS needle placement planning for robotic-assisted LDR seed brachytherapy - Fan, Yilun; Zhang, Xuehe; Liu, Lichen; Li, Changle; Yao, Chong; Zhao, Jie (Frontiers in Oncology, 2026)
IntroductionLow-dose-rate (LDR) seed brachytherapy treatment planning systems (TPSs) can generate dose-optimized seed distributions; however, translating these plans into robot-executable needle insertions introduces additional geometric, anatomical, and robotic constraints that may limit clinical feasibility.MethodsThis study presents an optimization framework for robotic-assisted LDR seed brachytherapy that refines needle trajectories based on preplanned seed distributions. The framework explicitly incorporates anatomical safety constraints and robotic feasibility requirements while aiming to preserve the original dosimetric quality.ResultsSimulation studies using thoracic and upper abdominal anatomical models show that the proposed method can generate clinically executable needle placements with minimal deviation from the planned seed positions. Phantom experiments further demonstrate the practical feasibility and placement accuracy of the optimized trajectories under robotic operating conditions.DiscussionThe proposed framework improves the feasibility and reproducibility of robotic-assisted LDR seed implantation in thoracic and related anatomical settings, offering a practical pathway toward safer and more reliable clinical deployment.